Kunniaa veisatkaa : joulukonsertti - Lahden Mieskuoro; Hynninen, Jorma; Karjalainen, Kari; Kiviniemi, Kalevi; Paasikivi, Lilli; Vesikko, Esa; Kiiski, Paavo (Lahden mieskuoro, 1995)
21 kappaletta.
Keywords: Lahden Mieskuoro : albumit